Taxonomy of water beetles in the genus Hydrochus Leach, 1817, from Bolivia, Brazil and Paraguay (Coleoptera: Hydrochidae) - Perkins, Philip D. (Zootaxa, 2021)
The taxonomy of Bolivian, Brazilian and Paraguayan water beetles in the genus Hydrochus Leach, 1817 is presented. The known fauna now consists of 77 species, 37 of which are described as new species. The new species are diagnosed, and high-resolution images of the habitus and male genitalia of each species are given, as are distribution maps. The following new species of Hydrochus are described: H. accinctus n. sp., H. amazonicus n. sp., H. ampliarmus n. sp., H. argutulus n. sp., H. artus n. sp., H. austrinus n. sp., H. canalis n. sp., H. casuarius n. sp., H. clandestinus n. sp., H. colossus n. sp., H. compactus n. sp., H. constrictus n. sp., H. curvus n. sp., H. diffusus n. sp., H. distinctulus n. sp., H. distinctus n. sp., H. diversus n. sp., H. forcipuloides n. sp., H. forcipulus n. sp., H. fritillus n. sp., H. irregularis n. sp., H. liquidus n. sp., H. longissimus n. sp., H. membraneus n. sp., H. personatus n. sp., H. potenspiculatus n. sp., H. pronotulus n. sp., H. quinarius n. sp., H. rectus n. sp., H. reticulatus n. sp., H. robustus n. sp., H. sculptissimus n. sp., H. triangularis n. sp., H. trituberculatus n. sp., H. usualis n. sp., H. velatus n. sp., H. xingu n. sp. New locality data are provided for the following species: H. alternatus Perkins, H. argutus Knisch, H. astrictus Perkins, H. baloghi Makhan, H. basilaris Perkins, H. bicarinatus Perkins, H. bisinuatus Perkins, H. bituberculatus Perkins, H. choennii Makhan, H. coeneni Makhan, H. collaris Perkins, H. cracentis Perkins, H. denarius Perkins, H. drakei Knisch, H. drechseli Makhan, H. ducalis Knisch, H. elsjeae Makhan, H. formosus Perkins, H. hellmani Perkins, H. iduae Makhan, H. jenniferiduae Makhan, H. kellymilleri Perkins, H. leei Perkins, H. lobatus Perkins, H. lobissimus Perkins, H. merkli Makhan, H. obscurus Sharp, H. pietersenae Makhan, H. piroei Makhan, H. pumilio Knisch, H. pupillus Orchymont, H. purpureus Knisch, H. radhakishunae Makhan, H. richteri Bruch, H. secretus Knisch, H. shorti Perkins, H. soekhnandanae Makhan, H. spanglerorum Perkins, H. tarsalis Chevrolet, H. variabilis Knisch, H. zicsii Makhan.